2021
DOI: 10.3389/fmicb.2021.664826
|View full text |Cite
|
Sign up to set email alerts
|

Multiple CheY Proteins Control Surface-Associated Lifestyles of Azospirillum brasilense

Abstract: Bacterial chemotaxis is the directed movement of motile bacteria in gradients of chemoeffectors. This behavior is mediated by dedicated signal transduction pathways that couple environment sensing with changes in the direction of rotation of flagellar motors to ultimately affect the motility pattern. Azospirillum brasilense uses two distinct chemotaxis pathways, named Che1 and Che4, and four different response regulators (CheY1, CheY4, CheY6, and CheY7) to control the swimming pattern during chemotaxis. Each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 68 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…A. brasilense has been observed to react with reverses and pauses and to modulate speed in response to chemical gradients (Zhulin and Armitage, 1993;Mukherjee et al, 2019). Numerous studies have revealed that the Che4 system modulates reversals by changing the rotation direction of the polar flagellum, while the Che1 system modulates swimming speed (Zhulin and Armitage, 1993;Bible et al, 2012;Mukherjee et al, 2016;Ganusova et al, 2021). In addition, the Che4 system, in concert with two orphan CheY proteins (CheY6 and CheY7), also modulates the pausing behavior, aerotaxis and the induction of swarming motility (Mukherjee et al, 2019;Ganusova et al, 2021).…”
Section: Chemotaxis Systems Controlling "Run and Reverse" Motilitymentioning
confidence: 99%
See 1 more Smart Citation
“…A. brasilense has been observed to react with reverses and pauses and to modulate speed in response to chemical gradients (Zhulin and Armitage, 1993;Mukherjee et al, 2019). Numerous studies have revealed that the Che4 system modulates reversals by changing the rotation direction of the polar flagellum, while the Che1 system modulates swimming speed (Zhulin and Armitage, 1993;Bible et al, 2012;Mukherjee et al, 2016;Ganusova et al, 2021). In addition, the Che4 system, in concert with two orphan CheY proteins (CheY6 and CheY7), also modulates the pausing behavior, aerotaxis and the induction of swarming motility (Mukherjee et al, 2019;Ganusova et al, 2021).…”
Section: Chemotaxis Systems Controlling "Run and Reverse" Motilitymentioning
confidence: 99%
“…Numerous studies have revealed that the Che4 system modulates reversals by changing the rotation direction of the polar flagellum, while the Che1 system modulates swimming speed (Zhulin and Armitage, 1993;Bible et al, 2012;Mukherjee et al, 2016;Ganusova et al, 2021). In addition, the Che4 system, in concert with two orphan CheY proteins (CheY6 and CheY7), also modulates the pausing behavior, aerotaxis and the induction of swarming motility (Mukherjee et al, 2019;Ganusova et al, 2021). The Che2 and Che3 systems do not appear to be involved in chemotaxis.…”
Section: Chemotaxis Systems Controlling "Run and Reverse" Motilitymentioning
confidence: 99%